Uma aplicação farmacotécnica do algoritmo de Horn & Schunck: Um estudo preliminar - Correa, Paulo Roberto [UNESP]; Fonseca Filho, Paulo Roberto da; Agostinho, Marcelo Rodrigues [UNESP]; Miranda, Jose Ricardo de Arruda [UNESP] (My University, 2010)
Alternate current Biosusceptometry (ACB) is a low-cost biomagnetic tool that has been successfully applied on pharmaceutical research in both in vivo and in vitro experiments to evaluate performance of solid dosage forms. The aim of this work was to evaluate the Horn & Shunck method to access tablet disintegration. The ACB used have seven pairs of detection coils and a pair of excitation coils to mensure the magnetic flux variation due ferromagnetic material (ferrite) approximation. The signals were amplified and digitalized to create images, which were restored by Wiener filter and had the optical flow estimation calculated by Horn & Schunck (HS) algorithm. All signals and images are processed and developed algorithm on Matlab. During the tests the five tablets (500mg ferrite, 375mg excipients, compression 10 to 50 kN) were on a becker in front of the ACB system and only touching the surface of the water.

Biosusceptometria de corrente alternada (BAC) é uma ferramenta biomagnética de baixo custo que tem sido aplicada com sucesso em pesquisas farmacêuticas em experimento in vivo e in vitro para validar o desempenho de comprimidos. O objetivo deste trabalho foi verificar a viabilidade da aplicação de fluxo óptico, especialmente o algoritmo de Horn & Schunck para avaliar a desintegração de comprimidos. A BAC utilizada tem sete pares de bobinas detectoras e um par de bobinas de excitação para medir a variação de fluxo magnético devido à aproximação de material ferromagnético (ferrita). Os sinais foram amplificados e digitalizados para criar imagens, as quais são restauradas pelo filtro de Wiener e tem o fluxo óptico calculado pelo algoritmo Horn & Schunck (HS). Todos os sinais e imagens foram processados e os algoritmos desenvolvidos em ambiente Matlab. Durantes os testes, os cinco comprimidos (500mg ferrita, 375mg excipientes, compressão 10 a 50 kN) estavam em um recipiente em frente ao sistema de BAC e apenas tocavam a superfície da água.
A pharmaceutical application of Horn & Shunck algorithm: a premilinary study
Keywords: Tablets; Magnetic; Image processing; Computer-assisted; Comprimidos; Magnetismo; Processamento de imagem assistida por computador